Platelet-rich plasma effects on degenerative disc disease: analysis of histology and imaging in an animal model - Gullung, Gregory B; Woodall, W Brinker; Tucci, Michelle A; James, Judy; Black, David A; McGuire, Robert A (Evidence-Based Spine-Care Journal, 2011)
Study design: Randomized controlled animal trial.Objectives: To analyze the early and late phase effects of platelet-rich plasma (PRP) injection into and around the damaged intervertebral disc using an animal model, and to evaluate the needle puncture technique in creating a degenerative disc model.Methods: The L4-L5 intervertebral disc of 18 adult Sprague-Dawley rats was injured with a 21-gauge needle. Animals received an immediate injection of PRP, or a delayed injection of PRP 2 weeks postinjury, or no further intervention (sham) (n = 6/group). Six uninjured controls were used. Magnetic resonance imaging (MRI) was performed for a control at time 0 and each group at 4 weeks postinjury, this allowed resolution of inflammation and an accurate assessment of healing. Specimens were collected from immediate PRP group at 2 and 4 weeks postinjury, and the delayed PRP group at 4 and 6 weeks postinjury. The sham and control specimens were collected at 2, 4, and 6 weeks postinjury. Each disc was sectioned and analyzed subjectively for overall structure, cellularity, and water content (utilizing MRI). Disc height was measured using descriptive statistics and one-way analysis of variance (ANOVA) with Tukey post hoc analysis. It was presumed both groups injected with PRP would have better outcomes than the sham group.Results: The sham group had clear degenerative changes with loss of organizational structure, empty space, fibrous tissue, and inflammatory cells, indicating needle puncture leads to degeneration. The PRP treated groups had fibers that were damaged with empty spaces and inflammatory cells. However, there was maintenance of the ring structure and the nucleus appeared to have a healthy central portion. Overall, both PRP - treated groups retained more normal morphologic features, contained fewer inflammatory cells, and had higher fluid content on MRI; however the effect was more pronounced in the immediate injection group. The disc height was significantly different in the sham and immediate injection group at the 4-week interval.Conclusions: This percutaneous needle puncture technique is an effective method for creating a degenerative disc model without posterior destabilization of the spine. The administration of PRP has a protective effect on damaged discs in the acute and delayed injection settings representing clinical treatment with PRP in the early versus late stages of the degenerative process. It appears that earlier intervention in the disease process would be more beneficial than PRP treatment of already severely degenerated discs.